Phenotypic identification of over 1000 isolates of anaerobic bacteria recovered between 1999 and 2008 in a major Costa Rican hospital - Rodríguez Cavallini, Evelyn (2011)
Because of limitations in infrastructure, the aetiology of infections caused by anaerobic bacteria is seldom determined in clinical laboratories of developing countries. This study reports on the identification of 1010 anaerobic bacterial isolates collected between 1999 and 2008 in a major Costa Rican hospital with the use of two commercial phenotypic systems (RapID 32A and API 20A). Approximately 60% of the isolates were Gram-positive and, among the 35 species of Gram-positive bacteria found, the genera Clostridium, Propionibacterium and Eggerthella, and anaerobic cocci predominated. Twenty eight species were found among 395 isolates of Gram-negative bacteria. Species of Bacteroides were very frequent, followed by species of Prevotella, Veillonella, Fusobacterium and Porphyromonas.